Focal dermal hypoplasia in a male - Leni George; Nisha Agrawal; Peter Hogan (PAGEPress Publications, 2011)
Focal dermal hypoplasia (FDH) is a rare mesoectodermal dysplasia syndrome characterized by cutaneous, skeletal, dental, ocular and soft-tissue defects. An X-linked dominant mode of inheritance with lethality in male subjects has been proposed. Only around 30 cases of FDH have been reported in male subjects. Live born affected males are mosaic for mutations in PORCN gene . We present the mosaic pattern of FDH  in a young boy.